2019
DOI: 10.21873/invivo.11604
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Gastrectomy for Elderly Gastric Cancer Patients

Abstract: Background/Aim: The benefits of gastrectomy for elderly gastric cancer (GC) patients remain unknown. The aim of this study was to evaluate the validity of gastrectomy. Patients and Methods: Patients who had R0 or R1 resection and diagnosed as pathological Stage I-III GC were enrolled in this study. Patients were classified according to age: Elderly group (≥80 years old), non-Elderly group (70-79 years old), Standard group (≤69 years old). Results: As the age raised, the number of comorbidities increased and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Of note, a lower hemoglobin level and performing total gastrectomy could significantly be associated with the occurrence of postoperative remote infections such as pneumonia. The overall complication rate after gastrectomy in GC patients over 80 years of age was reported to be 30.8% in a recent study (18). The present study demonstrated that complications with a Clavien-Dindo classification≥grade II were observed in 24.8% of patients, which is consistent with the results of previous reports on elderly GC patients (19,20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, a lower hemoglobin level and performing total gastrectomy could significantly be associated with the occurrence of postoperative remote infections such as pneumonia. The overall complication rate after gastrectomy in GC patients over 80 years of age was reported to be 30.8% in a recent study (18). The present study demonstrated that complications with a Clavien-Dindo classification≥grade II were observed in 24.8% of patients, which is consistent with the results of previous reports on elderly GC patients (19,20).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, postoperative pneumonia as a remote infection was observed in six patients (5.9%). Previous reports showed that postoperative pneumonia occurred in 3-10% of patients and was the most common complication in elderly patients (18)(19)(20). Pneumonia is one of the most important complications after gastrectomy, which could affect the period of hospital stay or the quality of life after discharge in elderly GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Fujiwara et al who prospectively enrolled 448 patients undergoing gastrectomy; more postoperative complications (especially respiratory complications), in-hospital deaths, and worse OS were observed in patients aged ≥80 [44]. Despite these findings, patient selection and optimization of fitness before gastrectomy are key factors to ensure successful and safe surgery in older patients [45,46].…”
Section: Management Of Localized Diseasementioning
confidence: 91%
“…In general, if ESD results in non-curative resection, additional gastrectomy should be recommended [ 14 ]. However, age is a potential risk factor for morbidity (10.1–19.4%), although the mortality rate (0–2.2%) does not significantly differ between the elderly and the non-elderly patients [ 15 , 16 , 17 , 18 , 19 ]. Other reports have shown that myocardial infarction and diabetes are risk factors for increased mortality after gastrectomy [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%